A Role for the Inflammasome in Spontaneous Labor at Term. (8th March 2016) - Romero, Roberto; Xu, Yi; Plazyo, Olesya; Chaemsaithong, Piya; Chaiworapongsa, Tinnakorn; Unkel, Ronald; Than, Nandor Gabor; Chiang, Po Jen; Dong, Zhong; Xu, Zhonghui; Tarca, Adi L.; Abrahams, Vikki M.; et al.
Abstract : Problem: Inflammasomes are signaling platforms that, upon sensing pathogens and sterile stressors, mediate the release of mature forms of interleukin (IL)‐1β and IL‐18. The aims of this study were to determine (i) the expression of major inflammasome components in the chorioamniotic membranes in spontaneous labor at term, (ii) whether there are changes in the inflammasome components associated with the activation of caspase‐1 and caspase‐4, and (iii) whether these events are associated with the release of the mature forms of IL‐1β and IL‐18. Method of study: Chorioamniotic membranes were collected from women at term with and without spontaneous labor. mRNA abundance and protein concentrations of inflammasome components, nucleotide‐binding oligomerization domain‐containing (NOD)1 and NOD2 proteins, caspase‐1, caspase‐4, IL‐1β, and IL‐18 were quantified by qRT‐PCR ( n  = 28–29 each), ELISA ( n  = 10 each) or immunoblotting ( n  = 8 each), and immunohistochemistry ( n  = 10 each). Active caspase‐1 and caspase‐4, as well as mature IL‐18, were determined by immunoblotting ( n  = 4 each), and pro‐ and mature forms of IL‐1β were determined by ELISA ( n  = 4–7 each). Results: Inflammasome components and NOD proteins were expressed in the chorioamniotic membranes obtained from women at term. The chorioamniotic membranes from women who underwent labor had (i) higher concentrations of NLRP3 (NOD‐like receptor family, pyrin domain‐containing protein 3) and NOD1 protein, (ii) greater immunoreactivity for caspase‐1 and caspase‐4, (iii) a greater quantity of the active form of caspase‐1 (p20), and (iv) higher mRNA abundance and protein concentrations of pro‐ and mature IL‐1β. However, mRNA abundance and protein concentrations of the mature form of IL‐18 were not increased in tissues from women who underwent labor at term. Conclusions: Spontaneous labor at term is characterized by the expression of inflammasome components, which may participate in the activation of caspase‐1 and lead to the cleavage and release of mature IL‐1β by the chorioamniotic membranes. These results support the participation of the inflammasome in the mechanisms responsible for spontaneous parturition at term.